Erratum: CATARINA DE L. ARAÚJO-SILVA & KIM LARSEN (2012) Tanaidacea (Tanaidacea: Crustacea) from Brazil. IV. A new genus and two new species from the family Leptocheliidae. Zootaxa, 3523, 1–19. - de L. Araújo-Silva, Catarina; Larsen, Kim (Zootaxa, 2012)
(Erratum)